siRNA therapeutics - Rossi, John; Rossi, Daniel J. (Henry Stewart Talks, 2022)
Introduction to RNA interference (RNAi), A history of siRNA, siRNAs as potential therapeutics, Limitations to siRNA therapeutics, Improving siRNA stability, Current and future siRNA drugs